Expressive bound morphemes in Malayalam speaking children with specific language impairment - Maria Grace Treasa; Shyamala K C (Journal of All India Institute of Speech and Hearing, 2013)
The present study aimed to investigate the emergence of expressive bound morphemes in 10 children, aged 3-8 years, with Specific Language Impairment (SLI) as compared to 10 chronological age (CA) controls. All the participants had a verbal repertoire of two-word phrases and were monolingual speakers of Malayalam. Expressive use of six different inflectional suffixes of Malayalam- 1./NDѥ/-Plural, 2./e/-Accusative, 3./il/-/RFDWLYH XҀH-*HQLWLYH NNΩ QΩ-Dative case markers and 6./um/Conjunction was examined using elicited Sentence Imitation Test in Malayalam (SIT-M) developed from our earlier research*. Results revealed that performance of SLI group was significantly (p<0.05) poorer than the CA group, suggestive of underlying morphological deficits. However, both the groups exhibited relatively better scores on Locative /il/, Dative /kke/ & /ne/ case markers and Plural  /kal/ than conjunction  /um/, Accusative  /e/ Genitive  /ute/ case markers. Implications for morphological assessment in Specific Language Impairment are also discussed,